Supporting Successful Multicultural Societies Education is Key to National Progress - Sage, Rosemary (UIN Sunan Gunung Djati Bandung, 2024)
Successful societies depend on everyone signing up to core values and actions. In multicultural settings the acceptance of differences in the way people operate has led to rules flouted, bringing chaos and conflict. Core to successful relationships are narrative language abilities, which enable creative as well as critical thinking to broaden and improve information processing and production. Critical, linear thinking analyses a situation, based on facts and data, whilst the creative, lateral approach develops new ideas and solutions. A study shows how language and thinking competencies have declined to hinder interactions between people - vital for new interdisciplinary job-roles now that technology is taking over routines. Focus on developing direct talk, to assist effective collaboration and learning is advocated. Training is required to appreciate language dual function to develop effectively, but also stratify people to potentially add to inequality if not aware. Most learning problems, at all student levels, are rooted in low levels of language, thinking and communication, which receive limited attention in teaching and training. The article looks at the background to thinking and expression and considers a route to more successful multicultural societies.